Building Together : Succesful Partnerships Between Community and the Health and Social Services System - Community Health and Social Services Network (CHSSN) (2017)
The Community Health and Social Services Network (CHSSN) coordinates a Quebec-wide health and social services “Adaptation Program” designed to enhance the vitality of English-speaking minority communities in Quebec by increasing access to existing health and social services for Englishspeaking Quebecers. The program is supported by an investment from Health Canada and has been undertaken in partnership with the ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English through partnerships between local English-speaking communities and health and social services system.
Keywords: Official Language Minority Community (OLMC)

Our Story : The New Carlisle Community Learning Centre Developmental Evaluation Report - Chatterton, Tammy; Legault, Emma (Leading English Education and Resource Network (LEARN), 2014)
The New Carlisle Community Learning Centre (NCHS CLC) is one of 37 community schools in Quebec. We are located in a small town on the Gaspesian Peninsula. Many people refer to the location as The Baie Des Chaleur. Our vibrant CLC is located in the town of New Carlisle, within New Carlisle High School. The centre was established to encourage lifelong learning by facilitating access to services and offering support to families, students and community members. The founders believed that a CLC would bridge the noticeable gaps in rural communities like ours, balancing the playing field so that our community would have the same opportunities as more fortunate and larger areas. Therefore, the CLC’s main goal is to link partners together to create a culture of lifelong learning that enhances the capacity of the population to live in healthy vibrant communities.

Community Portrait : New Carlisle - Richardson, Mary; Gauvin-Racine, Joëlle (Community Health and Social Services Network (CHSSN), 2012)
In 2009, the Community Health and Social Services Network (CHSSN) concluded an agreement with Quebec’s Institut national de santé publique (INSPQ) to develop knowledge on the English-speaking population of Quebec as part of a program concerning health projects for official language minority communities. Gaining a better understanding of English-speaking communities in Quebec is one of the objectives of that collaboration, and it is explored here through the lens of community development.
Keywords: Official Language Minority Community (OLMC)

Baseline Data Report 2009-2010 : Demographic Profiles of Quebec's English-speaking Communities by selected CSSS Territories - Pocock, Joanne; Warnke, Jan (Community Health and Social Services Network (CHSSN), 2010)
This document presents selected demographic characteristics of the English-speaking population of the CSSS territories in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI) of the Community Health and Social Services Network (CHSSN). The information presented is drawn from the 2006 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec's official language minoritty community.
Keywords: Official Language Minority Community (OLMC)